2010
DOI: 10.1577/t09-134.1
|View full text |Cite
|
Sign up to set email alerts
|

Common Carp Distribution, Movements, and Habitat Use in a River Impounded by Multiple Low‐Head Dams

Abstract: The common carp Cyprinus carpio is an introduced species that is abundant in many impounded rivers. We assessed habitat conditions and common carp abundance in three flowing sites and three impounded sites of the Fox River, Illinois, to examine factors that influence the success of common carp in these systems. Radiotelemetry was used to determine long-term movement and habitat use patterns of common carp among flowing and impounded areas. Impounded areas were wider and deeper than flowing areas and had lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 81 publications
3
17
0
Order By: Relevance
“…Poor habitat characterized by a deep pool, silty substrate, little to no surface velocity and little habitat heterogeneity stretches approximately half a kilometre above the Ellsworth Park Dam and approximately 1.5 km above the Danville Dam. These pools consistently had the lowest surface water velocity, while faster velocities were observed below both dams in the current study, a pattern also observed by Butler and Wahl () in the Fox River, Illinois. These data suggest that the presence of these low‐head dams strongly impacts both habitat quality and surface velocity in areas proximate to these structures.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Poor habitat characterized by a deep pool, silty substrate, little to no surface velocity and little habitat heterogeneity stretches approximately half a kilometre above the Ellsworth Park Dam and approximately 1.5 km above the Danville Dam. These pools consistently had the lowest surface water velocity, while faster velocities were observed below both dams in the current study, a pattern also observed by Butler and Wahl () in the Fox River, Illinois. These data suggest that the presence of these low‐head dams strongly impacts both habitat quality and surface velocity in areas proximate to these structures.…”
Section: Discussionsupporting
confidence: 86%
“…The linkage between habitat quality and surface water velocity with proximity to these impoundments are consistent with dam impacts noted in most systems (e.g. Kanehl et al, , Santucci et al, , Butler, Wahl, ). Poor habitat characterized by a deep pool, silty substrate, little to no surface velocity and little habitat heterogeneity stretches approximately half a kilometre above the Ellsworth Park Dam and approximately 1.5 km above the Danville Dam.…”
Section: Discussionmentioning
confidence: 76%
“…Selection for shallow depths and low to intermediate velocities, especially in response to higher flow, is known in several riverine fish species, including black basses (shoal bass, Stormer & Maceina ; Guadalupe Bass, Perkin et al. ), common carp (Butler & Wahl ), muskellunge (Brenden et al. ) and other lepisosteids (Helfman et al.…”
Section: Discussionmentioning
confidence: 99%
“…). Periods of low flow also reduce connectivity and can help in managing invasion potential of invasive species (Bunn and Arthington ; Butler and Wahl ). Furthermore, many fish species are commonly associated with refuge habitat in arid systems (Gilligan et al .…”
Section: Flow Delivery Scenariosmentioning
confidence: 99%